Tebelelo ya dingwalogare dipading tse di hlaotswego tsa O. K. Matsepe - Seanego, James (My University, 2022)
There is nothing new on earth. Every text is the repetition of another text, or other things already existing. This study reflects on the texts leaning thematically on other texts. It does so by critically examining the intertexts which shaped O.K. Matsepe’s four novels, namely Lešitaphiri (1963), Megokgo ya Bjoko (1968), Kgorong ya Mošate (1962) and Mahlatse a Madimabe (1981). By revealing the intertexts, it is hoped that a maximum understanding of the novels by this outstanding author is reached. Underpinned by intertextual theory, this study adopted a qualitative approach to allow a better understanding of the identified phenomena. The four novels were purposevily sampled due to their relevancy to the topic under discussion. The study employed content analysis to thoroughly analyse data which were collected using a document review method. The discussion and findings of the study clearly indicates that the Bible and culture are the two main sources which influenced Matsepe’s writing. This research contributes to the existing knowledge as it scrutinises Matsepe’s philosophical novels which are still relevant to the current epoch and beyond.
An intertextual reading of O. K. Matsepe's selected novels
Thesis (M. A. (Northern Sotho)) -- University of Limpopo, 2022
Keywords: Text; Intertext; Understanding; Bible; Culture; Influence and writing; Transmission of texts; Northern Sotho literature -- Criticism, Textual